Electroanatomical mapping after cardiac radioablation for treatment of incessant electrical storm: a case report from the RAVENTA trial - Kästner, Lena; Boda-Heggemann, Judit; Fanslau, Hannah; Xie, Jingyang; Schweikard, Achim; Giordano, Frank Anton; Blanck, Oliver; Rudic, Boris (Strahlentherapie und Onkologie, 2023)
Background Electroanatomical mapping (EAM)-guided stereotactic arrhythmia radioablation (STAR) is a novel noninvasive therapy option for patients with monomorphic ventricular tachycardia (VT) refractory to antiarrhythmic drugs and/or urgent catheter ablation (CA). Data on success rates in an emergency situation such as electrical storm (ES) are rare. We present a case of a patient with an initially very poor life expectancy after extensive myocardial infarction with therapy-resistant ES, not amendable for further antiarrhythmic drug therapy, implantable cardioverter-deﬁbrillator implantation, or repeated CA who was introduced to the radiation oncology department for emergency STAR as a bail-out therapy. - Methods Target volume deﬁnition and transfer from EAM to CT were validated and quality assured with a semi-automatic, dedicated visualization tool (CARDIO-RT). Emergency STAR was performed with 25 Gy in the framework of the RAVENTA study. The VT burden gradually decreased after STAR; however, a second VT morphology occurred, which was successfully treated with EAM-guided CA 12 days after STAR. - Results The second EAM-guided CA showed areas of low voltage in the irradiated segments, indicating a precise targeting and early functional response to STAR. The patient remained free of any VT recurrence or any radiation-related toxicities and in good general condition during the recent follow-up of 18 months. - Conclusion The case highlights the possible approach, caveats, difﬁculties, and prognosis of a patient severely affected by therapy-resistant VT in whom CA could not lead to VT suppression. Further studies of putative mechanisms of STAR in the acute and chronic phase of this novel therapy are warranted.